Synthesis and in-situ characterization of photochromic yttrium oxyhydride grown by reactive e−-beam evaporation. (September 2020) - Kantre, K.; Moro, M.V.; Moldarev, D.; Wolff, M.; Primetzhofer, D.
Abstract: We report on controlled growth of photochromic yttrium oxyhydride thin films monitored by in-situ composition depth profiling. Films were grown by reactive e − -beam evaporation and subsequently oxidized, while simultaneously tracking the oxygen and hydrogen concentrations. Sample composition and photochromic response were characterized in-situ using non-destructive ion beam analysis and image analysis, respectively – as well as complementary ex-situ ion beam methods, X-ray diffraction and optical spectrophotometry. We show that photochromic yttrium oxyhydride can be grown as yttrium dihydride, which is then oxidized to O/H ratios triggering the photochromic response. Graphical Abstract: Image, graphical abstract